Young age is not a predictor of disease specific survival in oral cancer: A multi-institutional study. (April 2021) - Oh, Lawrence J.; Satgunaseelan, Laveniya; Asher, Rebecca; Veness, Michael; Smee, Robert; Goldstein, David; Gopalakrishna Iyer, N.; Balasubramanian, Deepak; Low, Hubert; Palme, Carsten E.; Gupta, Ruta; Clark, Jonathan R.
Highlights: Age is not a predictor of disease related mortality in OSCC. Age alone does not indicate prognosis for OSCC patients. Prognosis is based on adverse clinicopathological features. Abstract: Background: Over the last few decades evidence has accumulated for increasing incidence of oral cavity squamous cell carcinoma (OSCC) in a younger cohort. Prior studies examining the effect of age at diagnosis on prognosis have produced conflicting data. Methods: A multi-institutional cohort study was performed across 6 different sites in Australia, Canada, India and Singapore. Disease-free (DFS), overall (OS) and disease-specific (DSS) survival were analysed. The association of the number of adverse features with survival outcomes was investigated. Results: From 3179 patients, age was a significant predictor of OS with patients older than 45 years having a 66% increased risk of death (HR 1.66, 95%CI 1.33 – 2.07, p < 0.001). The number of adverse features was a significant predictor of OS with 3 or more adverse features having a 199% increased risk (HR 2.99, 95%CI 2.61–3.43. p < 0.001). The estimate effect was greater in patients ≤ 45 years (HR 3.49 vs HR 2.81). Age was not a significant predictor of DSS with similar rates of death from OSCC in multivariable models. The number of adverse features was a significant predictor of DFS with ≥ 3 adverse features having a 140% increased risk of death. The number of adverse features was a significant predictor of DSS with ≥ 3 adverse features having a 230% increased risk of disease specific death. Conclusions: Age is not an independent predictor of disease specific mortality in OSCC. Differences in outcomes are due to the confounding effect of adverse clinicopathological features and the ability to tolerate surgery and adjuvant therapy.